Improving company value: the role of human capital, structural capital, capital employed, investment decisions, and manager's attitude to risk - Sumiati Sumiati; Risna Wijayanti; Pusvita Yuana; Choirul Nikmah (Universitas Negeri Surabaya, 2022)
Various studies show that companies and organizations have realized that knowledge-based capital is an important company asset. Managing the company's knowledge-based capital is one of the important tasks to encourage companies to compete with other companies. This study aims to identify the knowledge-based capital in human capital, structural capital, and capital employed by companies and its effect on investment decisions that affect company value. Through literature review, this concept also incorporates managers' risk attitude, which is part of ERM (Enterprise Risk Management) to develop the concept of Knowledge-based Risk Management (KBRM). Based on path analysis using AMOS, the result shows direct influence of human capital and capital employed on investment decisions is not significant. Meanwhile, the direct influence is significant. Investment decision does not mediate the relationship between human capital, structural capital, and capital employed on company value. Furthermore, managers' attitude to risk as risk-averse weakens the relationship between investment decisions and company value. Based on that result, companies need to reconsider managers’ behaviour in facing risks so that managers able to take risks when deciding on investments in the future and increase the value of the company.